Analisis Kemampuan Berpikir Kreatif Matematis Siswa SMP Ditinjau Dari Karakteristik Tanggung Jawab - Nindi Sri Rahayu; Hikmatul Khusna (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
This study is a qualitative descriptive study, which aims to describe the mathematical creative thinking ability of middle school students from the characteristics of high, medium and low students' sense of responsibility. By using purposive sampling technique, the subject of this research consisted of 3 students. Data collection techniques in this study used test and non-test techniques using instruments supporting the characteristics of responsibility, mathematical creative thinking ability test I, interview guidelines, and mathematical creative thinking ability test II. Data analysis in this study includes data reduction, data representation and data conclusions.There are differences in mathematical creative thinking abilities between students with the characteristics of high, medium, and low level student responsibility. Indicators of mathematical creative thinking ability can be achieved by students with high responsibility characteristics. Meanwhile, students with medium and low responsibility characteristics have not been able to achieve the four indicators of mathematical creative thinking.Â Keywords: Mathematical creative thinking, responsibility characteristics.